La incidencia de la disgrafía durante el proceso de enseñanza y aprendizaje en los niños y niñas de quinto año de educación general básica de la escuela de educación básica “Isabel la Católica”, recinto Cuatro Esquinas, parroquia Guanujo, cantón Guaranda, provincia Bolívar, período 2023. - Andrade Carvajal, Diana Julisa (2023)
Currently, one of the most frequent problems in basic education is the difficulty that some children have with writing. Dysgraphia is a disorder that affects handwriting skills, difficulty taking dictation, copying texts, and writing freely. The present investigation analyzes the incidence of dysgraphia in the teaching and learning process in boys and girls in the Fifth Year of Basic General Education of the "Isabel la Católica" School of Basic Education, Cuatro Esquinas Campus, Guanujo parish, Guaranda canton, Bolívar province, during the period 2023. The study population consisted of 24 girls and boys and the teacher. Two questionnaires and a dictation were applied. The results showed that the most common mistakes made by boys and girls are related to spelling errors, punctuation marks, substitution of letters or words, difficulty maintaining good handwriting and spacing, as well as difficulties in maintaining a regular writing pattern. The teacher has observed some cases of dysgraphia in the group of students and has taken measures to correct these problems using fine motor techniques, specific calligraphy exercises and individualized follow-ups. Five strategies are proposed as part of the pedagogical material for the prevention of dysorthography (difficulties in spelling and writing), grasping dysgraphia (way of holding the pencil) and figural dysgraphia (writing with cut letters